2014
DOI: 10.1155/2014/598654
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells in Sepsis

Abstract: Sepsis is a systemic, deleterious host response to widespread infection. Patients with sepsis will have documented or suspected infection which can progress to a state of septic shock or acute organ dysfunction. Since sepsis is responsible for nearly 3 million cases per year in China and severe sepsis is a common, expensive fatal condition in America, developing new therapies becomes a significant and worthwhile challenge. Clinical research has shown that sepsis-associated immunosuppression plays a central rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 67 publications
0
30
0
Order By: Relevance
“…Thus, early activation of MDSCs during sepsis can be protective but at late stages may lead to the stage of immunoparalysis that proves detrimental to host. Thus, the exact role of MDSCs in sepsis as a friend or foe is still a topic of debate [243][244][245]. However, activation of MDSCs via TLR3, TLR7, TLR8 and TLR9 ligands (i.e.…”
Section: Myeloid-derived Suppressor Cells (Mdscs) In Inflammatory Dismentioning
confidence: 99%
“…Thus, early activation of MDSCs during sepsis can be protective but at late stages may lead to the stage of immunoparalysis that proves detrimental to host. Thus, the exact role of MDSCs in sepsis as a friend or foe is still a topic of debate [243][244][245]. However, activation of MDSCs via TLR3, TLR7, TLR8 and TLR9 ligands (i.e.…”
Section: Myeloid-derived Suppressor Cells (Mdscs) In Inflammatory Dismentioning
confidence: 99%
“…Resuscitation with HTS could induce dramatic early migration and redistribution of MDSCs from bone marrow to peripheral circulation, compared to resuscitation with NS or HES (Lu et al, 2013). The two major subpopulations G-MDSC and M-MDSC have different immunosuppressive mechanisms (Lai et al, 2014;O'Connor et al, 2015;Ost et al, 2016). Normally, G-MDSCs could differentiate into neutrophile granulocyte, while M-MDSC could differentiate into monocyte.…”
Section: Fig 3 Variations Of Mdscs and M-mdsc/g-mdsc Ratio In Mice Bmentioning
confidence: 99%
“…Other studies had also verified the inhibitory function of MDSCs in several chronic infections and autoimmune diseases (Makarenkova et al, 2006). Nevertheless, recent studies even suggested that the expansion of MDSCs in some acute inflammatory processes, such as burns and sepsis, could enhance immune surveillance and innate immune responses, which might be helpful in infection control (Brudecki et al, 2012;Lai et al, 2014;Ost et al, 2016). Additionally, it also implied that MDSCs have divergent gene expression profiles and functions in early and late sepsis.…”
Section: Fig 3 Variations Of Mdscs and M-mdsc/g-mdsc Ratio In Mice Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in patient management and supportive care have drastically improved patient survival through this hyper-inflammatory phase which is subsequently followed by an immunosuppressive phase. Following the cytokine storm, there is a marked decrease in host immunity including apoptosis-induced loss of innate and adaptive immune effector cell populations as well as an increase in immune suppressor cell populations, including T regulatory cells (Tregs) and myeloid-derived suppressor cells (MDSCs) (17)(18)(19)(20). With improvements to patient care, sepsis has transitioned from a hyper-inflammatory disorder to an immunosuppressive disorder, with almost 70% of deaths occurring after the initial inflammatory phase due to the subsequent impaired immunity that make patients more vulnerable to infection recurrence or nosocomial infections (21).…”
Section: Introductionmentioning
confidence: 99%